MANAJEMEN PENGELOLAAN PROGRAM TEKNOLOGI IDU (KARTU ID CARD SANTRI) UNTUK MEMANTAU UANG BELANJA SANTRI DI PONDOK PESANTREN DARUL ULUM KUBU RAYA - Samiyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Boarding School Darul Ulum Kubu Raya is an Islamic educational institution that has a large population of students. In this era of globalization, every educational institution, especially pesantren that are full of extra-curricular activities, are challenged to be able to utilize efficient technology so that they can achieve all activity targets precisely, quickly, and correctly, because pesantren are still the ideal education system for many people. This research uses a qualitative method with a case study approach. The research location is at the Darul Ulum Kubu Raya Islamic Boarding School located on Jl. Rasau Jaya, Limbung, Sungai Raya Sub-District, Kubu Raya Regency, West Kalimantan. This research data consists of primary data and secondary data. In this context, the IDU or Santri ID Card technology program is implemented to overcome some of the problems that exist in the previously used manual management system. The use of IDU (Kartu ID Card Santri) technology in monitoring students' spending money at Pondok Pesantren Darul Ulum Kubu Raya provides significant benefits in efficiency and financial management. With the IDU card, the payment process becomes easier and more transparent. Keywords: Management, IDU (Santri ID Card, Santri Shopping Money)